The export performance of selected electrical and electronic products in Malaysia / Aryati Salim - Salim, Aryati (Faculty of Business and Management, 2007)
Malaysia was one of the leading exporters in electrical and electronic products nowadays. A speech by Dato' Seri Rafidah Aziz, the Minister of International Trade and Industry, at the launching of the Malaysia International Trade and Industry (MITI) Report 2005, stated that , in 2005, the export of manufacturing products was comprised for 77.4% of total Malaysia's exports and lead by the electrical and electronic products that accounted for 64.1%. However, there is also competition from the other countries, especially from the emerging countries such as the People's Republic of China, Latin Countries , South Korea, Hong Kong as well as the European Union (EU). Moreover, due to the growing popularity of green concept in European Union (EU), these regions has adopted a number of directives for environmental protection that may have impact on the sales of electrical and electronic products. It also includes the restrictions on batteries and accumulators that contain mercury , the Directive on Waste Electrical and Electronic Equipment (WEEE) that have been implemented in August 2005, as well as the Directive on Restriction of Hazardous Substances (RoHS) in July 2006 (Profiles of Hong Kong Major Manufacturing Industries, 2007). This study was done to analyse the trend analysis of the selected electrical and electronic products in Malaysia as well as the competitiveness of these products using the Revealed Comparative Advantage (RCA) (Fatimah Mohd. Arshad). This indicator is divided into two ratios which are Net Export/Total trade Ratio and also Export Performance Ratio. The data involved for this study was from the year 2001 until 2005. From the results, it showed that mostly the trend analysis for seven selected electrical and electronic products were fluctuated except for the products of thermionic valves and tubes, photocells , etc., electrical apparatus for electrical circuits and printed circuits ; and electrical machinery and apparatus which shown the increasing trends. Moreover, most of the products also shown the significant of total export for Malaysia except for certain products that include thermionic valves and tubes, photo cells, etc., electrical apparatus for electrical circuits and printed circuits; and electrical power machinery and parts that gave the negative results. While, for the export performance ratio, electrical machinery and apparatus; and electrical power machinery and parts show the ratio below than one. It means that these products do not give the significant contribution for their markets.